PERAN GURU DALAM MENUMBUHKAN PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SDN 177 PEKANBARU - Beta Salsabilla; Zaka Hadikusuma Ramadan (STKIP Subang, 2023)
Problems related to cleanliness often occur in students at school. Schools carry out several parts in implementing a clean and healthy life but have not been implemented perfectly so that the role of the teacher is needed in encouraging students to live a clean and healthy life. The purpose of this research is to describe the teacher's role in cultivating clean and healthy living behaviors in students and implementing clean and healthy living behaviors. The method used in this research is descriptive qualitative. Data collection techniques are using interviews, observation and documentation. The data source involved 4 teachers and 2 students. Testing the validity of the data using triangulation. Data analysis techniques namely data reduction, data presentation and drawing conclusions. The results showed that the teacher's role is needed in cultivating clean and healthy living behavior in students at school even though it is not perfect in its implementation. The teacher's obstacles in fostering clean and healthy living behavior in schools lie in a lack of understanding related to implementing clean and healthy living, lack of facilities, lack of awareness of the students themselves and there should be support from people around them. The conclusion from the research results is that the teacher's role is said to be very important in fostering clean and healthy living behaviors in students where students need direction and giving good examples every day so that clean and healthy living behaviors are carried out. The role of the teacher that can be applied is as an educator, motivator, facilitator, demonstrator and evaluator to improve and optimize the implementation of clean and healthy living behaviors in schools. The role of the teacher is very much needed in the formation of students' clean and healthy living behavior because many students imitate or listen to directions and orders from their teacher directly.